Consumer Spending Perceptions On Changes In Macroeconomic Conditions - Rubianto Pitoyo; Afriany Afriany (GOVERNORS, 2026)
This study aims to clarify consumer spending perceptions on products affected by geopolitical issues in the period 2024 to 2025. The research method uses a qualitative approach in the form of a survey using a Likert scale. Purposive sampling is used, with 120 customers of  KFC products as the sample.   The findings in this study are that consumers still view brands, product quality, and services as the main considerations. The increase in Value Added Tax has a significant impact because it causes a surge in purchase prices. Meanwhile, geopolitical issues and increased inflation are not the main considerations that determine consumer spending. The results of this study indicate that consumer trust is a vital element in maintaining business stability and resilience, especially amidst socio-political changes and uncertain economic conditions. Meanwhile, flexible and adaptive marketing strategies can be a solution to address the challenges of macroeconomic change and business sustainability.